2006
DOI: 10.1007/s00239-006-0045-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomic Analysis of Human and Chimpanzee Indicates a Key Role for Indels in Primate Evolution

Abstract: Sequence comparison of humans and chimpanzees is of interest to understand the mechanisms behind primate evolution. Here we present an independent analysis of human chromosome 21 and the high-quality BAC clone sequences of the homologous chimpanzee chromosome 22. In contrast to previous studies, we have used global alignment methods and Ensembl predictions of protein coding genes (n = 224) for the analysis. Divergence due to insertions and deletions (indels) along with substitutions was examined separately for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
52
2
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 25 publications
5
52
2
2
Order By: Relevance
“…However, indels seem to be responsible for more than 3% of the differences (71). Thus, the overall divergence between the chimpanzee and human genomes is closer to 4% (74,75). In this respect, the retroviral insertion shared by the DRB2 and DRB6 pseudogenes behaves as expected and displays lower similarity values.…”
Section: Resultsmentioning
confidence: 69%
“…However, indels seem to be responsible for more than 3% of the differences (71). Thus, the overall divergence between the chimpanzee and human genomes is closer to 4% (74,75). In this respect, the retroviral insertion shared by the DRB2 and DRB6 pseudogenes behaves as expected and displays lower similarity values.…”
Section: Resultsmentioning
confidence: 69%
“…Short insertions and deletions (indels) account for a significant amount of the variation in mammalian genomes and are likely to make an important contribution to species-specific traits (Britten 2002;Wetterbom et al 2006). Their importance for medical genetics is highlighted by the fact that they have been implicated in a wide range of human diseases, the archetypal example being the phenylalanine deletion at position 508 in the CFTR protein that results in cystic fibrosis (Riordan et al 1989).…”
mentioning
confidence: 99%
“…Whilst SNPs are informative and relatively easy to identify, studies on model species have shown that insertion-deletion polymorphisms (indels) also play an important role in genome evolution and adaptation [73][74][75][76]. Identifying indels from high-throughput sequencing data remains a difficult bioinformatic problem [77], and identifying large indels in RRS data is especially difficult because only a small percentage of the genome is sequenced.…”
Section: Methods For Generating Genomic Datamentioning
confidence: 99%